2023
DOI: 10.3390/fermentation9040322
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Fermentation of Soybean Meal with Edible Mushroom Mycelium to Improve Its Nutritional, Antioxidant Capacities and Physicochemical Properties

Abstract: Soybean meal is a class of by-products obtained from the processing of soybean products. Despite its high nutritional value, the presence of glycoside isoflavones limits human use of soybean meal. This study evaluated the effect of solid-state fermentation (SSF) with different edible mushroom mycelia (Pleurotus ostreatus, Hericium erinaceus, and Flammulina velutipes) on the proximate composition, antioxidant properties, and physicochemical properties of fermented soybean meal powder (SP). The results revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Sporulation was easily obtained during SSF, but the resulting products had a limited shelf life. As the mechanisms of action of microorganisms on plants are elucidated, the production of higher value-added products such as antibiotics, enzymes, and proteins may be the future trend of SSF development [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…Sporulation was easily obtained during SSF, but the resulting products had a limited shelf life. As the mechanisms of action of microorganisms on plants are elucidated, the production of higher value-added products such as antibiotics, enzymes, and proteins may be the future trend of SSF development [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…The fermented soybean meal exhibited improved nutritional value, with Pleurotus ostreatus standing out among the three species. The study emphasized the enhanced protein content, increased glutamate and aspartic acid concentrations, and significantly higher antioxidant activity after fermentation [4].…”
mentioning
confidence: 86%
“…Among them, trypsin inhibitors, lectins and phytic acid are the most common. Trypsin inhibitors inhibit trypsin activity in monogastric animals and are essential for protein digestion, which cause poor feed conversion and growth performance (Wang et al ., 2023b). Lectins can bind to intestinal cells and cause inflammation, immune response and intestinal damage (Wang et al ., 2020).…”
Section: The Main Composition Of Fermented Soybean Mealmentioning
confidence: 99%
“…Wang et al . (2023b) used mycelium to ferment soybean meal and found that the generated hydrolase could catalyse the release of conjugated phenolic compounds and improve the antioxidant activity of soybean meal. Other studies have found that fermented soybean meal may reduce oxidative stress in lactating and pregnant sows by increasing the content of soybean isoflavones (Feizi et al ., 2022).…”
Section: Biological Activities Of Fermented Soybean Mealmentioning
confidence: 99%